(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper presents a new system for measuring the accuracy of mechanical clocks with Swiss Movement. Mechanical watches are complex devices consisting of many miniature components. Even small deviations in accuracy can lead to significant differences in timekeeping. Testing the accuracy of mechanical watches is an important process that ensures their functionality, durability, and value. It helps maintain a high level of precision in timekeeping, which is critical in many aspects of daily life and professional activity. The developed system provides a readily applicable alternative to measure and improve the accuracy of watches using a personal computer and acoustic analyses. The proposed methodology contributes to expanding the possibilities of investigating the dynamic characteristics of mechanical watches.